(untitled) (ESMAT Magazine, 2019)
This article discusses the topic of culpability for vulnerability from the Critical Criminology of the Argentine jurist Eugenio Raúl Zaffaroni, who had influence in this doctrinal construction in Brazil. The purpose of the text is to show that culpability for vulnerability is tied to the selectivity of the arbitrary penal system that satisfies the punitive power of the state. The selectivity shows that penalties can not be legally grounded because they have political meaning, mainly due to the unequal treatment of whites and blacks by the penal system. The solution to crime is not to repress the less favored social strata, under the penalty of disrespecting Human Rights, but to reduce the degree of selectivity and to think of Criminal Law as a form of contrasselectivity to rescue the isonomy of the penal system, among them the in the criminal dosimetry of this reality. The debate runs through the implementation of alternatives to mass incarceration, starting with a criminal policy that distinguishes crimes of lesser offensive potential from violent ones.